Fluid characteristics in hydrothermal veins of the Twangiza-Namoya Gold Belt, South Kivu and Maniema Provinces, DRC - Reid, Wesson Kyle (Rhodes University, Faculty of Science, Department of Geology, 2020)
This study evaluates fluid variations in hydrothermal quartz veins from gold deposits in Kamiuga, Lugushwa and Namoya, located in the Twangiza-Namoya Gold Belt (TNGB) of the Kibara Belt in the eastern Democratic Republic of the Congo (DRC. Petrographic, fluid inclusion (FI) microthermometric observations and Raman spectroscopy provided qualitative and quantitative fluid composition data on the hydrothermal and magmatic fluids and their evolution during mineral precipitation. The formational fluids, based on genetically specific characteristics, were categorized into six distinct FI Types. Type 1 to 4 FIs are common in all TNGB fluids. Type 1 and 2 FIs are high salinity halite bearing FIs that indicate formation fluids that are predominantly metamorphic-sedimentary in source. CO2 vapour-bearing and the aqueous-saline CO2 liquid-bearing Type 3 FIs commonly contain CH4 and/or N2. Type 4 FIs are saline aqueous and commonly co-genetic with Type 1 and 2 FIs. Type 5 CO2-rich FIs contain either sulphide crystals, amorphous or crystalline carbon. Type 3 and 5 FIs indicate fluid sources rich in organic materials. Type 6 single aqueous-liquid phase FIs have no apour bubble, lacked a visible phase change on heating and were not thermometrically evaluated. The data indicated a high correlation between fluid composition and gold grades. High Au grade veins correlate with CO2 bearing Type 3 and 5 FIs -predominantly liquid-bearing CO2 fluids and quartz veins and fluids that contain increased organic material and sulphides. The polyphase quartz veins show highly variable homogenisation and formational temperatures exceeding 400Â°C. Formation conditions indicate high trapping temperatures in relation to the pressures at which fluids were captured. The high depth-temperature gradients are likely associated with mesothermal orogenic go ld deposition. Mineralisation is interpreted to have taken place as a result of mobilisation of fluids during the Pan African orogeny. Based on fluid petrography and microthermometry, gold mineralisation is most likely associated with secondary fluid influx from metamorphic sedimentary sourrces such as metapelites. The correlation between high gold grades and secondary fluids containing sulphides, high depth-temperature gradients, elevated CO2, CH4 and organic materials suggest black shales as a possible primary fluid and gold source. The development of variable and multiple fluid influx events and interactions with host rocks and imported materials resulted in complex polyphase quartz veins; the product of which created viable gold deposits throughout the TNGB. The six FI Types provides evidence of the diversity in the formation and evolution of gold deposits in the TNGB.
Keywords: Gold ores -- Geology -- Kivu (Congo : Region); Mineralogy -- Congo (Democratic Republic); Hydrothermal deposits -- Congo (Democratic Republic); Quartz -- Congo (Democratic Republic)